Vadba hoje na tekočem traku s pomočjo robota pri bolnikih z multiplo sklerozo, nezgodno poškodbo možganov ali Parkinsonovo boleznijo - pregled literature - Krizmanič, Tatjana (Rehabilitacija (Ljubljana), 2012)
Background: The use of robotic devices could help physiotherapists to achieve higher intensity of locomotor training in patients with injuries or diseases of the nervous system. A literature review was conducted with the aim to present the results of the studies which have evaluated the effects of locomotor training with robotic assistance in patients with multiple sclerosis, traumatic brain injury or Parkinsons disease. Methods: We performed a systematic review based on the PubMed bibliographic database. We included all articles published from 1990 to 2011 that evaluated the effectiveness of robotic technology in improving walking ability in adult patients with multiple sclerosis, traumatic brain injury or Parkinsons disease. All the studies included in the review examined the effect of locomotor training on walking function with one of the following roboticassisted devices: Lokomat, Electromechanical Gait Trainer or LokoHelp. Conclusion: The studies reported on the effectiveness of walking training with robotic assistance regarding overground velocity and walked distance in patients with multiple sclerosis or Parkinsons disease. No significant differences were detected between locomotor training with robotic assistance and conventional walking training. There is limited evidence that locomotor training with robotic assistance is beneficial in patients with traumatic brain injury.
Keywords: Brain injuries; hoja; multipla skleroza; Multiple sclerosis; Parkinson disease; Parkinsonova bolezen; poškodbe možganov; rehabilitacija; Robotics; robotika; vocational rehabilitation; Walking